Financial literacy and economic uncertainty: impact on sme financial performance in cirebon regency - Maulana, Hilman; Yuniarto, Rival Fahara; Maiyaliza, Maiyaliza (Institute of Computer Science (IOCS), 2025)
Economic uncertainty is a major challenge for Small and Medium Enterprises (SMEs) in maintaining financial stability and business sustainability. This study aims to analyze the impact of economic uncertainty on the financial performance of SMEs in Cirebon Regency and assess the role of financial literacy in moderating the relationship. A quantitative method was used in this study with a data collection technique through a questionnaire distributed to 100 SME owners. Data analysis was carried out using descriptive statistics and multiple linear regression with the help of SPSS software. The results show that economic uncertainty has a negative and significant effect on the financial performance of SMEs, with a regression coefficient value of -0.376 (p = 0.000). Meanwhile, financial literacy has a positive influence on the financial performance of SMEs, with a regression coefficient of 0.482 (p = 0.000). The regression model used explains the 37.5% variation in SME financial performance, which shows that other factors also contribute to SME financial performance. Thus, this study confirms that increasing financial literacy can be an effective mitigation strategy for SMEs in the face of economic uncertainty. The implications of this study lead to the importance of financial education for SME owners to improve their ability to manage their finances and anticipate unexpected economic changes. In addition, this study also provides recommendations for the government and financial institutions to develop training programs and access to more flexible financing for SMEs so that they are more resilient in facing economic challenges.